PENGARUH PENINGKATAN BERAT BADAN SELAMA KEHAMILAN TERHADAP BERAT BADAN BAYI BARU LAHIR DI BIDAN PRAKTEK MANDIRI (BPM) PAULINA BUKITTINGGI TAHUN 2014 - Sari, Yade Kurnia; Suryani, Arinda (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
Hospitalization is a taste of crisis in children when a child is sick and hospitalized so it must adapt to the hospital environment. Causes of anxiety are influenced by factors of officers, as well as the new environment. Overcoming anxiety in this toddler children, nurses need to provide relaxation therapy that one of them is by using music. Music is a medical therapy where the objective is to improve the physical, emotional, cognitive, and social for people of all ages. The purpose of this study is determining whether there is the effect of music therapy on anxiety levels of children toddler who experienced hospitalization at the hospitals Dr. Achmad Mochtar Bukittinggi in 2016. This research is a Quantitative research design experimental with pretest-postest way design and sampling method with accidental sampling that 20 people. Collecting data using by questionnaire and data processing is done with a paired T-test statistical test using a computerized system. The results of this research that the average value of differences in levels of anxiety before and after the intervention was 9,40 and p-value 0,0001 < Î± 0,05 which occurs, decrease levels of anxiety after the intervention